2010
DOI: 10.3139/146.110300
|View full text |Cite
|
Sign up to set email alerts
|

Effect of surface charges on the polarization distribution in ferroelectric nanotubes

Abstract: The stable polarization distributions of freestanding ferroelectric nanotubes with different surface charges are investigated numerically using a phase field model based on the time-dependent Ginzburg – Landau equation. For a nanotube without surface charges, a pure vortex structure is formed as a result of the energy minimization. When the uniform surface charges are applied on the upper and lower surfaces, the out-of-plane components become nonzero. The out-of-plane components of polarizations are found to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…1 It has been found that low-dimensional ferroelectrics, such as ferroelectric nanodots, 2-7 ferroelectric nanotubes, 8,9 and ferroelectric thin films, 10 exhibit polarization vortices or vortexlike domain structures in order to reduce the depolarization energy. The polarization vortices are bistable and can be switched from one state to the other, which holds a promise to increase the density of ferroelectric nonvolatile random access memories by several orders of magnitude.…”
mentioning
confidence: 99%
“…1 It has been found that low-dimensional ferroelectrics, such as ferroelectric nanodots, 2-7 ferroelectric nanotubes, 8,9 and ferroelectric thin films, 10 exhibit polarization vortices or vortexlike domain structures in order to reduce the depolarization energy. The polarization vortices are bistable and can be switched from one state to the other, which holds a promise to increase the density of ferroelectric nonvolatile random access memories by several orders of magnitude.…”
mentioning
confidence: 99%